Perilaku Hidup Bersih Dan Sehat Pada Anak Usia Sekolah Dasar - Wahyu Nur Indah Sari; Mulyadi Mulyadi (Pedir Research Institute, 2021)
Abstrack: Clean and healthy living behavior (PHBS) has the intention of motivating children to play an important role in realizing health and fitness and one of the targets for developing a health environment is school. The problems to be answered through this research are: 1. What is the teacher's strategy in implementing clean and healthy living behavior in elementary school age children at Madrasah Ibtidaiyah Miftahul Ulum Sidowungu? and 2. What are the teacher's obstacles in implementing clean and healthy living behavior for elementary school age children at Madrasah Ibtidaiyah Miftahul Ulum Sidowungu?. This study uses a qualitative method with a special study approach. Data collection techniques using interviews, observation, and documentation. The data analysis technique uses the theory in Miles and Huberman's book, tests the validity of the data by triangulation and adequacy of references. clean and healthy living behavior, conducting clean Friday activities, providing hand sanitizer, providing adequate cleaning tools along with sufficient water and soap supplies. 2) the implementation includes: giving students an understanding of clean and healthy living behavior, always reminding before and after carrying out activities they are required to wash their hands, apply discipline, carry out a clean and healthy lifestyle. 3) Evaluation. While the obstacles faced have solutions to solve them.